ADORNO, FANON E AS DINÂMICAS DE VIOLÊNCIA E EMANCIPAÇÃO: a dialética das encruzilhadas. - CINTIA MEDEIROS ROBLES (2025)
This study is part of the activities of the Research Group "Formation and Culture in Contemporary Society – EduForP/CNPq" and the Research Program "Critical Theory for Nonconformity: Non-Identity as the Telos of Ethnic and 'Racial' Relations," funded by CNPq/MCTI/FNDCT (Call 18/2021 – Universal). Linked to the research line "Education, Culture, Society" of the Graduate Program in Education at the Federal University of Mato Grosso do Sul, the study examines violence as a threat to human emancipation through the dialogue between Theodor W. Adorno and Frantz Fanon. The research proposes the "dialectic of crossroads" as an analytical tool to articulate the relationships between conformity and rupture in understanding the dynamics of violence. Methodologically, it adopts Grounded Theory to analyze the works Studies in the Authoritarian Personality (Adorno et al., 2019) and The Wretched of the Earth (Fanon, 2022), expanding the scope to other fundamental texts by the authors. Drawing from Adorno’s critique of conformity and Fanon’s perspective on violence as a praxis of rupture, the study investigates how violence operates structurally in shaping subjects and reproducing inequalities. The results indicate that while Adorno understands violence as a mechanism for maintaining authoritarian social order, Fanon analyzes it as a means of subverting oppressive structures. However, the study demonstrates that both approaches converge in viewing violence as a structuring phenomenon of social relations, establishing an intersection in their critique of domination. The dialectic of crossroads highlights that the opposition between conformity and rupture is not binary but is traversed by historical and contextual complexities that challenge a simplistic reading of violence. The study concludes that the dialectic of crossroads contributes to a broader understanding of violence as a social phenomenon, allowing discussions to move beyond fixed and dichotomous categories. This theoretical shift provides support for deepening the critical analysis of violence in its relationship with education, suggesting new pathways for constructing theoretical alternatives that do not reproduce the traps of conformity or absolute destruction.